'Antigone', 'Medea', 'Ariadne', 'Semele' and 'Jocasta'. Issue 2 (1st June 2021) - Spinosa, Dani
These pieces are from my porn myth series: 'Antigone', 'Hestia' and 'Medea' were first published in a pamphlet from Happy Monks Press, and 'Ariadne' and 'Semele' were created for the Concrete Is Porous second gallery show.